Continent‐scale strike‐slip on a low‐angle fault beneath New Zealand's Southern Alps: Implications for crustal thickening in oblique collision zones. (18th September 2015) - Lamb, Simon; Smith, Euan; Stern, Tim; Warren‐Smith, Emily
Abstract New Zealand's Southern Alps lie adjacent to the continent‐scale dextral strike‐slip Alpine Fault, on the boundary between the Pacific and Australian plates. We show with a simple 2‐D model of crustal balancing that the observed crustal root and erosion (expressed as equivalent crustal shortening) is up to twice that predicted by the orthogonal plate convergence since ∼11 Ma, and even since ∼23 Ma when the Alpine Fault formed. We consider two explanations for this, involving a strong component of motion along the length of the plate‐boundary zone. Geophysical data indicate that the Alpine Fault has a listric geometry, flattening at mid crustal levels, and has accommodated sideways underthrusting of Australian plate crust beneath Pacific plate crust. The geometry of the crustal root, together with plate reconstructions, requires the underthrust crust to be the hyperextended part of an asymmetric rift system which formed over 500 km farther south during the Eocene—the narrow remnant part today forms the western margin of the Campbell Plateau. At ∼10 Ma, the hyperextended margin underwent shallow subduction in the Puysegur subduction zone, and then was dragged over 300 km along the length of the Southern Alps beneath a low‐angle (<20°) section of the Alpine Fault. We speculate that prior to 10 Ma, more distributed lower crustal shortening and thickening occurred beneath the Southern Alps, accommodating southward extrusion of continental crust in the northern part of the plate boundary zone, providing a mechanism for clockwise rotation of the Hikurangi margin.